PENGARUH KARAKTER WIRAUSAHA TERHADAP MINAT BERWIRAUSAHA SISWA KELAS XI PEMASARAN DI SMK MANDIRI PONTIANAK - Elma Atika Putri; Bambang Genjik Sumartono; Warneri Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to determine the "The Influence of Entrepreneurial Character on the Entrepreneurship Interest in Marketing class Students at SMK Mandiri Pontianak". The method used in this research was quantitative descriptive method in the form of correlational study. The population in this study was all student of the class XI Marketing at SMK Mandiri Pontianak. While the samples in this study were grade XI students obtained through Census Sample technique. The researcher applied indirect communication and documentary study as the data collection technique with 35 respondents. So, the degree of freedom df = n-k or 35-2 = 33, then t-table was 1.692.  By this result, it was compared between t-count and t-table. It was concluded that t-count > t-table (4.962> 1.692). It indicated that Ha was accepted and Ho was rejected. The determination coefficient in the results of the study showed the contribution of influence between the independent variable and the dependent variable by 42.7%, while the remaining 57.3% was influenced by other factors which were not examined by the researcher. So the conclusion is that there is an Influence of Entrepreneurial Character on Entrepreneurship Interest in Marketing Class Students in SMK Mandiri Pontianak.Keywords: Entrepreneurial Character, Entrepreneurial Interest